The Correlation between Apparent Diffusion Coefficient Value on MRI and the Pathology Consistency of Meningioma - Wyka Faulani Hafizah Nur; Widiana Ferriastuti; Bambang Soeprijanto (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Preoperative evaluation of meningioma consistency is important because it will affect surgical procedures, surgical optimization, risk assessment, and patient management. The consistency of meningioma can be predicted by Apparent Diffusion Coefficient (ADC) value on MRI. ADC values are useful in quantitative tumor assessment based on diffusivity in the tumor. The objective of the study is to find out the correlation between ADC value and the pathology consistency of meningioma.Methods: A retrospective study was carried out using medical records at Dr. Soetomo General Hospital, Surabaya by January 2017 - December 2018. The ADC value was obtained by placing three ROI in the tumor and the consistency was obtained from the results of the pathology examination, followed by the Spearman correlation test.Results: There The tumor range value of ADC was 0.58 x 10-3mm2 s to 1.63 x 10-3mm2/s. The mean ADC value in soft, intermediate, and hard consistency was 1.247+ 0.200 x 10-3mm2/s, 0.950 + 0.453 x 10-3mm2/s, and 0.793 + 0.161 x 10-3mm2/s, the cut-off value of ADC was + 0.822 x 10-3mm2/s with specificity 68% and sensitivity 85%, the AUC is 0.740 with a significance value of 0.0043 (p<α, α = 0.05). It was obtained an ADC correlation with the consistency of meningioma, the significance value is p=0.000 (p<α, α = 0.05).Conclusion: There is a correlation between the ADC value and the consistency of meningioma. The ADC value can be considered for an optimal preoperative evaluation in assessing the consistency of meningioma.